Thirty years in the making: A critical overview of the Kura-Araxes periodization from a radiocarbon perspective - Passerini, Annapaola (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The chronology of the Kura-Araxes culture has long been a matter of debate, particularly as regards its internal periodization. To date, two main periodization systems have been proposed, which argue, respectively, for a three-part and two-part scheme. Despite the acquisition of new 14C and archaeological datasets, universal consent on this issue still hasn’t been reached. This paper reviews the state of the art in chronological studies on the Kura-Araxes culture and provides a critical assessment of the two periodization systems since the introduction of radiocarbon dating in the South Caucasus. The discussion demonstrates that the understanding of the Kura-Araxes chronology exceeds mere questions of ‘objective’ chronometric agreement, as seen in the way that different archaeological agendas have influenced the interpretation of ambiguous calibrated data, and vice versa. Finally, the paper highlights the potential of Bayesian chronological modeling to disambiguate chronometric evidence and exploit archaeological knowledge to the benefit of regionalized periodization frameworks.